2015
DOI: 10.1007/s13224-014-0651-z
|View full text |Cite
|
Sign up to set email alerts
|

“Informed” Consent: An Audit of Informed Consent of Cesarean Section Evaluating Patient Education and Awareness

Abstract: Introduction Better diagnosis and early referral due to increased health care coverage have increased the cesarean deliveries at tertiary-care hospitals of India. Improvements in the health care system raise many concerns and need of cross-checking system in place to counter the problems pertaining to patient education and participation of patient. While most of the cesarean sections are done in good faith for the patient, it does not escape the purview of consumer awareness and protection. Materials and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 1 publication
2
9
0
Order By: Relevance
“…When nurses expressed their experiences, it was found that they ignored patient rights to receive information about the disease and their treatment, and accordingly, they were unable to select an appropriate treatment, so that this issue could cause irreparable complications for the patient. This issue has also been stated in the study by Kirane et al ( 46 ). According to their study, it was reported that only a quarter of the patients had received appropriate description about the procedures and their complications.…”
Section: Discussionsupporting
confidence: 62%
“…When nurses expressed their experiences, it was found that they ignored patient rights to receive information about the disease and their treatment, and accordingly, they were unable to select an appropriate treatment, so that this issue could cause irreparable complications for the patient. This issue has also been stated in the study by Kirane et al ( 46 ). According to their study, it was reported that only a quarter of the patients had received appropriate description about the procedures and their complications.…”
Section: Discussionsupporting
confidence: 62%
“…Several reports have recognised weaknesses in the process of acquiring surgical informed consent for obstetric procedures, such as providing no explanation of the indication for surgery, procedure-related risks or the postoperative trajectory 7–16. Women may feel pressured into undergoing surgery when little information is provided or information is not understood 9 14.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in most cases, the patient signs the form as a witness or do not sign it at all. A study in India reported that the IC forms are mostly signed by the relatives, not by the patients, and their relatives are informed before the surgery [9].…”
Section: Discussionmentioning
confidence: 99%
“…In case of CS, surgical IC is considered as an ethical and legal requirement. It provides information about the potential benefits and risks of CS, alternative therapy, and anesthesia options [9,10]. A recent metaanalysis reported that women with CS are at higher risk of maternal death and postpartum infection [2].…”
Section: Introductionmentioning
confidence: 99%